2014
DOI: 10.1093/chemse/bjt060
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Binding of an Odor Within Olfactory Receptors: A Precursor to Receptor Activation

Abstract: Using computational methods, which allow mechanistic insights at a molecular level, we explored the olfactory receptor (OR)-odor interactions for 2 mouse ORs, S79 and S86. Both ORs have been previously experimentally, functionally characterized. The odors used were mostly carboxylic acids, which differed in chain length, substituents on the primary carbon atom-chain and degree of unsaturation. These odors elicited varied activation responses from both ORs. Our studies revealed that both receptors have 2 distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The OR bundle is finally built under the constraint of the 7.5 Å resolution rhodopsin template. Alternatively, the use of a homology protocol can be considered as a starting point for building the TM domains prior to a refinement based on optimization of hydrophobic packing [103,104].…”
Section: Molecular Modeling Of Ormentioning
confidence: 99%
“…The OR bundle is finally built under the constraint of the 7.5 Å resolution rhodopsin template. Alternatively, the use of a homology protocol can be considered as a starting point for building the TM domains prior to a refinement based on optimization of hydrophobic packing [103,104].…”
Section: Molecular Modeling Of Ormentioning
confidence: 99%
“…12 Residues involved in the dynamic process that converts an inactive OR structure into an active one are still elusive. This article is a step forward in their identification.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, each OR TM helix that results from homology modeling is "relaxed" from its template-structure artifacts using molecular dynamics simulation in a hydrated environment before being reinserted into the OR helical scaffold. 27,28 Once the helical model is built, the helices have to be rotated such that the hydrophilic side of the helix is pointed inwards towards the putative binding region, while the hydrophobic side is pointed outwards. Different approaches have been used to rationalize these helical rotations.…”
Section: Or Protein Model Buildingmentioning
confidence: 99%
“…While most studies have shown a preferred binding region for ORs is bound by TM helices 3, 4, 5 and 6, 25,27,31,[33][34][35] another less preferable binding region has also been identified, bound by helices 1, 2, 6 and 7. 28 A computational study showed that docking in this region is likely to be inhibitory, while binding in the preferred region is likely to lead to OR excitation.…”
Section: Odorant Dockingmentioning
confidence: 99%
See 1 more Smart Citation